The problem of defection from the Catholic Church in the German Federal Republic - GÓRALSKI, WOJCIECH (Prawo Kanoniczne, 2015)
The introduction of a clause of formal act of defection from the Catholic Church to Code of Canon Law, explained by the Pontical Council for Legislative Texts in 2006 and then abolished by pope Benedict XVI in 2009, was of no signicance for the legal regulation in force in German Federal Republic. As a result of historical circumstances existing in this country, the only way to formally defect from the Catholic Church is still Kirchenaustritt declared at a state authority, which is – as stated in 2006 by the country’s Episcopal Conference of German Federal Republic – a crime tantamount to schism, for which the prescribed penalty is excommunication latae sen- tentiae. However, an essential novum occurred in the General Decree of Episcopal Conference of German Federal Republic from 2012: the mention of excommunication was omitted (declaring its incurrence became depen- dent on the assessment of the act Kirchenaustritt: whether it constituted an act of schism, heresy or apostasy). is modication should be regarded as positive, just like Pastoral Letter (Pastorales Schreiben) developed by the German Bishops and attached to the General Decree. It is necessary to emphasize that the problem of assessment – on canon law basis – of statement of defection from the Catholic Church as the only way to exempt from the church tax, is still open to dispute (inter alia ger- man milieu).